Development of an Internet of Things-Based Medical Equipment Asset Tracking System Using ESP32 and GPS NEO-6M - Danang Kristioko Legowo; Muhtar; Lili Ruhyana; Gunawan; Abdul Firman; Mulyatno; Adrian Dwichaya (Jurnal Teknologi Informatika dan Komputer, 2026)
Medical assets are important components in supporting healthcare operations; therefore, their management requires a fast and integrated tracking system. This study aimed to design and test an Internet of Things-based medical equipment asset tracking system using an ESP32 microcontroller, NEO-6M GPS module, Wi-Fi connection, PHP-MySQL server, and a web-based digital map interface. The research used a Research and Development method involving needs analysis, hardware and software design, prototype implementation, and testing of connectivity, location accuracy, data transmission, database integration, and web interface performance. The results showed that the ESP32 connected to Wi-Fi within 5-10 seconds, transmitted data using HTTP GET every 10 seconds, and achieved outdoor GPS accuracy of approximately +/-3 meters. In indoor conditions or environments obstructed by conductive materials, accuracy decreased to more than 15 meters or the position was not detected. The system successfully stored location data in MySQL and displayed medical equipment markers in real time. This system is feasible as an asset monitoring prototype, with further development recommended for indoor localization, area notifications, and online server deployment.